Case Report: A case of ultra-late recurrence of KIF13A-RET fusion non-small cell lung cancer response to selpercatinib - Park, Ha-Young; Park, Joo-Heon; Shin, Myung-Geun; Han, Seung Jung; Ji, Yong-Sok; Oh, Hyung-Joo; Kim, Young-Chul; Lee, Taebum; Choi, Yoo-Duk; Oh, In-Jae (Frontiers in Oncology, 2023)
Background Cancer recurrence remains a significant problem, and most postoperative recurrences of non-small cell lung cancer (NSCLC) develop within 5 years after resection. We present a rare case of ultra-late recurrence of NSCLC accompanying choroidal metastasis with KIF13A-RET fusion 14 years after the definitive surgery. Case description A 48-year-old female patient who had never-smoked presented with decreased visual acuity. She had been treated with right upper lobe lobectomy followed by adjuvant chemotherapy 14 years prior. Fundus photographs revealed bilateral choroidal metastatic lesions. Positron emission tomography-computed tomography (PET-CT) scans showed extensive bone metastases and focal hypermetabolism in the left uterine cervix. An excision biopsy of the uterus showed primary lung adenocarcinoma with immunohistochemistry of TTF-1+. Plasma next-generation sequencing (NGS) identified the presence of KIF13A-RET fusion. After 6 months of selpercatinib therapy, PET-CT revealed a partial response for bone and uterine metastasis and stable disease for choroidal lesions. Conclusion In this case report, we are reporting a rare case of ultra-late recurrence of NSCLC in a patient with choroidal metastasis. Furthermore, the diagnosis of NSCLC with RET fusion was based on liquid-based NGS rather than tissue-based biopsy. The patient showed a good response to selpercatinib, which supports the efficacy of selpercatinib as a treatment for RET-fusion-positive NSCLC with choroidal metastasis.